Sistem Peringatan Dini dalam Kegiatan Pencegahan Kebakaran Hutan di KPH Kuningan, Jawa Barat - Bambang Hero Saharjo; Saqif Khazimastasia (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2019)
Forest fire caused many negative effects so that preventive action is highly needed. One of preventive action is determining vulnerable area of forest fire. Rate of society perception based on research in several village in KPH Kuningan to the warning system were belongs to high for Cihanjaro village, and medium for Simpayjaya village, and low for Kawungsari village. According to the accessibility, Kawungsari village has highest access to the forest. There are several variables of forest fire such as distance of society housing to the forest, accessibility to forest, and potential area for conflict. Determination of forest fire vulnrable area could be considered from society perception to the KPH Kuningan existence and warning system in the forest fire preventive action. Key words: forest fires, early warning system, determination prone areas